2012
DOI: 10.1007/s00590-011-0936-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with avascular necrosis of the femoral head and nonunion in patients younger than 65 years with displaced femoral neck fractures treated with reduction and internal fixation

Abstract: Patients between 53.5 and 65 years presented a higher risk of AVN. A primary arthroplasty should be considered in this subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 22 publications
0
17
2
1
Order By: Relevance
“…In the present study we observed that nonunion rate was 16%, which shows resemblance to the studies in literature. However, on the contrary to these studies [ 4 , 22 , 27 - 30 ], we observed that femoral head necrosis rate was much lower (6.4%). Schweitzer et al reported that femoral head necrosis rates in patients range from 50 to 65 years old are more when compared to younger patients, and this is not related to timing of the surgery.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the present study we observed that nonunion rate was 16%, which shows resemblance to the studies in literature. However, on the contrary to these studies [ 4 , 22 , 27 - 30 ], we observed that femoral head necrosis rate was much lower (6.4%). Schweitzer et al reported that femoral head necrosis rates in patients range from 50 to 65 years old are more when compared to younger patients, and this is not related to timing of the surgery.…”
Section: Discussioncontrasting
confidence: 99%
“…When literature is reviewed, it is maintained that the relation between nonunion and femoral head necrosis was not fully understood [ 26 ]. In literature, there are some studies indicating when an early intervention is required, through which methods a full anatomic reduction and stable fixation could be obtained and whether capsulotomy or joint aspiration in order to diminish pressure in the capsule, yet they have not achieved a consensus [ 4 , 22 , 27 - 30 ]. Also, cultural characteristics, race, nutrition and age are some of the predictive factors in femoral neck fractures [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is strong evidence in the literature that increasing age is associated with impaired fracture healing [ 2 , 21 , 22 ]. Femoral neck HR decreased with age, both in displaced (p < 0.001) and non-displaced (p < 0.003) fractures [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among patients under age 60, just 7 of 106 had fracture nonunion (HR = 93.4%); among patients age 70 to 80 years, 84 of 337 had nonunion (HR = 75.1%) [ 2 ]. In a separate study, patients with displaced femoral neck fracture who developed nonunion were significantly older than patients with normal healing [ 21 ]. Nevertheless, in a third study, age was not identified as a predictor of nonunion in 202 patients with intracapsular femoral neck fracture [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In relatively young adults, it often results from high-energy injury, and its incidence is much less common than in elderly patients. The most frequently encountered complications after surgery are loss of reduction, fracture nonunion and avascular necrosis of the femoral head [1][2][3][4][5][6][7][8][9][10][11]. In the elderly, hemiarthroplasty is frequently performed to obtain post-operative stability and an early return of mobility.…”
Section: Introductionmentioning
confidence: 99%